03.26 Early mouse interferon-alpha1 overexpression in vivo triggers an expansion of highly suppressive regulatory t lymphocytes protecting against experimental arthritis. (1st March 2017) - Ribon, Matthieu; Matyja, Katarzyna; Hervé, Roxane; Lemeiter, Delphine; Tsumiyama, Ken; Shiozawa, Shunichi; Boissier, Marie-Christophe; Bessis, Natacha; Decker, Patrice
Abstract : Background: Type I interferons (IFN-I) can be both anti- and pro-inflammatory. Their role is controversial in rheumatoid arthritis (RA) and experimental models. A not-understood IFN-I signature has been reported in RA patients. In mice, IFN-I enhance/inhibit arthritis according to IFN subtype and arthritis models/kinetics. We have evaluated the effects of early IFN-α production in collagen-induced arthritis (CIA) which mimics RA. Materials and methods: CIA was induced by 2 immunizations with collagen/CFA. Disease development was studied in conditional transgenic mice over-expressing mouse IFN-α1 (Tet-off system) and in IFN-α1-negative littermates. Arthritis was followed by clinical evaluation. Inflammation/bone destruction were estimated by histology. Plasma cytokines/anti-collagen antibodies were measured by Luminex/ELISA. Lymphocyte sub-populations were analysed by flow cytometry. Bone marrow cells were cultured with M-CSF/RANKL to study osteoclasts. CD4 + CD25 + regulatory T cells (Treg) and CD4 + CD25 - effector T cells (Teff) were purified by magnetic sorting. ATPase activity was determined in vitro by a luminescent assay. Treg inhibition of Teff proliferation was measured by flow cytometry in co-cultures. The in vivo therapeutic capacity of purified Treg was estimated by adoptive transfer. Results: Induction of mouse IFN-α1 production before the first or between the two immunizations resulted in CIA protection, in contrast to IFN-α1 induction after both immunizations. Both immunised IFN-α1 - and IFN-α1 + mice produced anti-collagen antibodies, however the latter produced less. IFN-α1 + mice produced less IL-6 but more IL-5. Protection in IFN-α1 + mice was associated with decreased polarisation to Th17 and increased polarisation to Th1/Th2 lymphocytes and IFN-γ-positive NK cells. Osteoclast differentiation/activity were decreased in IFN-α1 + mice. Particularly, CIA protection in IFN-α1-overexpressing mice was associated with an in vivo expansion of Treg with a higher ectonucleotidase CD39 expression, higher ATPase activity and a higher capacity to inhibit Teff. Most importantly, adoptive transfer of those highly suppressive Treg purified from CIA IFN-α1 + mice impaired CIA development in IFN-α1 - recipients in comparison to adoptive transfer of Treg purified from CIA IFN-α1 - mice. Conclusions: This is the first study evidencing a potent therapeutic window in which IFN-α1 protects against CIA. Protection is associated with an expansion of more suppressive Treg able to confer protection upon adoptive transfer.